Ratoon Pigeon Pea An alternate source of income for rainfed farmers - Somasundaram, J; Singh, R K; Kumar, Ashok; Sinha, N K; Patra, A K (Indian Farming, 2018)
The pigeon pea crop not only enriches soil through its nitrogen fixing capacity but also adds soil organic carbon through its higher leaf litters. In addition to main crop yield, additional yield of ~660 and 780-kg/ha pigeon pea grain yield was recorded during first and second season, respectively. This was 10-18% higher than previous season yield. Moreover, application of 5-10t/ha FYM increased yield by 33% during first season and 37% in second season. Therefore, ratoon pigeon pea is a potential alternative to be used as an intercrop in low input rainfed farming systems of semi-arid India.